INDUSTRIAL RELATION PROBLEMATICS DURING THE COVID-19 PANDEMIC: ASSESSING THE EFFECTIVENESS OF MEDIATION AS DISPUTE SETTLEMENT PROCESS - Nyoman Satyayudha Dananjaya; Longtan SHI; Kadek Agus Sudiarawan; Putu Ade Harriestha Martana; Made Shannon Tjung (Jurnal Bina Mulia Hukum, 2022)
The failure to produce a peace agreement as an implementation of the bipartite process open up opportunity for the parties to resolve their disputes by the tripartite stage. At this stage, although the parties are given the opportunity to choose the settlement model used either through arbitration, conciliation or mediation, in general, the parties have a tendency to choose the settlement model through mediation facilitated by the Manpower Office based on process efficiency. The purpose of this study is to identify and determine the characteristics of industrial relations disputes that occur in the tourism sector during the Covid-19 pandemic, to identify and find out the obstacles that occur in the implementation of industrial relations dispute mediation in the tourism sector during the Covid-19 pandemic, to measure and analyze how effective mediation is in resolving industrial relations disputes in the tourism sector during the Covid-19 pandemic besides to find and formulate efforts that can be made to strengthen the position of mediation as an alternative dispute resolution in industrial relations. The method used in this study is an empirical legal research method with a conceptual approach and a case approach.